Vietnam : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix reviews the factors behind developments in government revenue in Vietnam during 1996-2000. This period encompasses Vietnam's continued transition to a market-based economy, the Asian financial crisis in 1997, and, toward the end, high world oil prices, which have led to both temporary and permanent changes in the revenue base. The paper discusses developments in foreign currency deposits (FCDs) as a proxy for dollarization. It also reviews the FCD trends, analyses the causes, and assesses the benefits and policy challenges.